1978
DOI: 10.3168/jds.s0022-0302(78)83583-8
|View full text |Cite
|
Sign up to set email alerts
|

Change in Udder Health with Overmilking

Abstract: Removing milker units as soon as milk flow stopped was compared to milking for a fixed time of 12 min in an 8-wk trial with 60 cows. Teats were dipped in broth culture of approximately 10(9) colony forming units per ml of Staphylococcus aureus, Streptococcus agalactiae, and Streptococcus uberis for 4 wk. More new infections of quarters occurred in the 12-min group. In trials 2 and 3, 20 additional cows were milked with automatic milking machine detachers and 20 cows were milked with a flow control unit for 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…The same observation was presented by Oliver et al (1956) as applying to all infections. However, opposite opinions about the age distribution have been presented as well (Rendel and Sundberg 1962, Schalm et al 1971, Natzke et al 1978. According to studies of Erb and Martin (1978) the incidence of acute mastitis has proved to be independent of age.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…The same observation was presented by Oliver et al (1956) as applying to all infections. However, opposite opinions about the age distribution have been presented as well (Rendel and Sundberg 1962, Schalm et al 1971, Natzke et al 1978. According to studies of Erb and Martin (1978) the incidence of acute mastitis has proved to be independent of age.…”
Section: Agementioning
confidence: 99%
“…10-20 minutes' overmilking resulted in the increase of the cell content and oedema in the teat wall but did not cause more marked clinical symptoms (Walser 1966). Although mucous membrane injuries can be detected in the teat canal as a result of overmilking (Peterson 1964), and though the use of an automatic cluster remover can lead to a lower CMTreading and to less erosion of the teat ends, compared with ordinary milking (Philpot 1972), no definite proof has been found in the controlled studies that overmilking increases the number of infections (Seelemann and Obiger 1959, Kingwill et al 1977, Brandsma and Maatje 1978, Natzke et al 1978. The lower percentage of infections in the front quarters, though they are subjected most to overmilking, is considered to be practical proof of the little effect overmilking exercises (Kingwill et al 1977).…”
mentioning
confidence: 99%
“…Overmilking at high vacuum levels (57-70 kPa) had no effect on new infections, clinical mastitis or udder irritation in heifers (Mochrie et al 1953;Neave et al 1962) or in previously uninfected cows (Olney & Mitchell, 1983). Natzke (1978) and Natzke et al (1978) compared normal milking and overmilking with and without large vacuum fluctuations and concluded that if overmilking is associated with mastitis the effects appear to be small.Milking with short teatcup liners resulted in about twice the new infection rate (NIR) of quarters milked with liners of normal length, but the experimental differences were confined mainly to front quarters (Mein et al 1983). Although many controlled experiments have failed to show that overmilking seriously affects mastitis (see reviews by Fell, 1964;Dodd & Neave, 1968;Natzke, 1978;Schultze, 1979), it was thought that this interaction in treatment response to pulsation failure between front and hind quarters could be associated with more overmilking on the front quarters.…”
mentioning
confidence: 95%
“…Overmilking at high vacuum levels (57-70 kPa) had no effect on new infections, clinical mastitis or udder irritation in heifers (Mochrie et al 1953;Neave et al 1962) or in previously uninfected cows (Olney & Mitchell, 1983). Natzke (1978) and Natzke et al (1978) compared normal milking and overmilking with and without large vacuum fluctuations and concluded that if overmilking is associated with mastitis the effects appear to be small.…”
mentioning
confidence: 95%
“…Among the studies of factors for occurrence of mastitis, there are many reports concerning milking procedures (Natzke et al . ; Galton et al . , , ; Rasmussen et al .…”
Section: Introductionmentioning
confidence: 99%